Procedimientos de control de bienes de larga duración y su incidencia en la información financiera. Guía de procesos para el levantamiento de la información financiera para el Gobierno Provincial de Cotopaxi. - Vizuete Achig, Marcela Patricia (2011)
This work is the design of a process guide for the picking up of financial information in the Provincial Government of Cotopaxi, because the entity did not have an adequate system for the management, control and custody of long term assets; which caused the processes to be carried out empirically. Administrative penalties for failing the laws and regulations, and the lackness of helpful, reliable financial information. The project is supported by practical and theoretical-scientific basis, in using descriptive research and an experimental metodology in which interviews are designed to work with officials of the entity. To make it feasible the use of this guide; the procedures for the various receipts and expenditure of goods, as well as flow charts, activities and forms, are described in order to make it easy to understand. In the perspective adopted here, if a department that does not implement adequate internal controls, will run the risk of deviations in the operations and of course the decisions are not the right ones for its management. It may lead to operate it in a crisis, so it should be assumed a number of consequences that affect the results of the activities. That is why the main aim of developing this guide of procedures is to assist officials by establishing a set of rules and procedures to ensure the resources efficiently, and effectively. Obtaining consistent data on accounting information will help to make correct decisions in the management of public funds, so it is clear that these changes can be achieved by implementing and adapting internal controls, which are able to safeguard and preserve the assets of the institution.